2020
DOI: 10.1039/d0ra06299e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evaluation of oxygen vacancies-enhanced photogeneration of the superoxide radical in nano-TiO2 suspensions

Abstract: Reactive oxygen species (ROS) play an important role in the photocatalytic degradation of pollutants and are closely related to the surface defects of a semiconductor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 47 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…93% (Figure C), which is much higher than that of benzoquinone and tryptophan. Considering that the vacancies on TiO 2 nanoparticles could activate the dissolved oxygen to O 2 •– for oxidizing luminol, we directly injected the ZnO nanoparticles with oxygen vacancy into luminol in the absence of H 2 O 2 . The CL signals of luminol-dissolved O 2 –ZnO with oxygen vacancy were rather weak and almost the same as blank (Figure S12), which indicated that the ZnO with oxygen vacancy did not activate the dissolved O 2 into O 2 •– .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…93% (Figure C), which is much higher than that of benzoquinone and tryptophan. Considering that the vacancies on TiO 2 nanoparticles could activate the dissolved oxygen to O 2 •– for oxidizing luminol, we directly injected the ZnO nanoparticles with oxygen vacancy into luminol in the absence of H 2 O 2 . The CL signals of luminol-dissolved O 2 –ZnO with oxygen vacancy were rather weak and almost the same as blank (Figure S12), which indicated that the ZnO with oxygen vacancy did not activate the dissolved O 2 into O 2 •– .…”
Section: Resultsmentioning
confidence: 99%
“…As a further step, to prove the general applicability of the CL strategy, we also used this method to evaluate the oxygen vacancy in TiO 2 and WO 3 . We prepared a series of TiO 2 nanoparticles 34 and WO 3 nanosheets 55 with different oxygen vacancies. As shown in Figure 6A, the CL intensity of TiO 2 is TiO 2 -1 > TiO 2 -2 > TiO 2 -3 > TiO 2 -4 > TiO 2 -5 > TiO 2 -6 in the luminol−H 2 O 2 system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To suppress this photodecomposition, we developed a UV-A-insensitive TiO X ETL for NFA-based OPVs by a novel blending method. Although the wide bandgap TiO X ETL was already reported for OPVs in previous works, the synthetic route for its precursor solution, which followed the conventional synthetic process that uses a three-necked flask for reflux in Ar-filled conditions, has problems such as being time-consuming and having poor reproducibility. ,, Moreover, the fabricated TiO X ETL showed a notorious light-soaking problem that resulted in a decreased PCE of OPVs, thereby limiting its usage to only fullerene-based OPVs. Herein, by adding a small amount of water during the blending process for preparing the TiO X precursor solution, we induced a prehydrolysis step to increase the Ti–O–Ti connectivity, which led to a dense gel network in a film form. As shown in Figure S4, X-ray photoelectron spectroscopy (XPS) spectra show that the intensity of Ti 3+ ions, which is correlated to the defect in the TiO X film, decreased with the addition of water in Ti 2p spectra. Accordingly, the intensity of lattice oxygen (O L ) increases and the intensity of −OH bond and oxygen vacancy (O V ) decreases with the addition of water in O 1s spectra. ,, By using TiO X as the ETL, we obtained high-performance NFA-based OPVs, even showing no light-soaking problem (see the detailed information in the device performance part in the experimental section and in the Supporting Information). As shown in Figure b, we confirmed that the newly fabricated TiO X film (E g ∼3.68 eV) has a higher optical bandgap than that of the glass/ITO substrate (3.67 eV).…”
Section: Resultsmentioning
confidence: 99%